Improving phenolic content in Piper betel leaf extract via pH adjustment during ethanol extraction - Urmatul Waznah; Nuniek Nizmah Fajriyah; Windha Widyastuti; Rizqi Aulia Rachim; Mutiara Zahra Romadhona; Bunga Merrelita Syahputi; Eko Mugiyanto (Universitas Ahmad Dahlan, 2026)
The extraction efficiency of bioactive compounds from Piper betel leaves is strongly influenced by pH conditions. Understanding the impact of pH on the recovery of phenolic and flavonoid compounds is crucial for optimizing extraction processes. This study aimed to evaluate the effect of extraction pH on the yield of total phenolic and flavonoid compounds from Piper betel leaves and to analyze the correlation between total phenolic and flavonoid compounds under different pH conditions. Ethanol extraction was performed at various pH levels (2, 4, 6, 8, and 10). Total flavonoid content was determined using quercetin equivalents (mg QE/g extract), while total phenolic content was measured as gallic acid equivalents (mg GAE/g extract). Hierarchical cluster analysis and correlation analysis were applied to assess the relationships among extraction profiles. The results showed that pH 2 achieved the highest flavonoid yield (22.60 ± 0.92 mg QE/g), whereas pH 4 resulted in the maximum phenolic content (59.51 ± 1.88 mg GAE/g). Alkaline conditions (pH 8 and 10) significantly reduced extraction efficiency. Cluster analysis distinguished pH extremes (2 and 10) from intermediate pH values (4–8), while correlation analysis revealed a strong positive relationship (r = 0.98) between phenolic and flavonoid content at pH 6. Negative correlations were observed at pH 2, 8, and 10, indicating competitive extraction dynamics. Extraction pH critically determines the recovery and profile of phenolic and flavonoid compounds in Piper betel extracts. Acidic conditions (pH 2–4) are optimal for maximizing bioactive compound yields, while pH 6 offers a balanced extraction of both phenolic and flavonoid groups. These findings provide a scientific basis for pH-controlled extraction strategies in the development of phytopharmaceutical products.